Pengaruh Audit Tenure, Likuiditas, Solvabilitas Dan Profitabilitas Terhadap Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Andre Prayoga; Annisa Nauli Sinaga (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study is to discuss whether there is an effect of audit tenure, liquidity, solvency and profitability on going concern audit opinions on manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The research method used is quantitative research that uses secondary data and data collection techniques for documentation studies. The population collected was 169 companies, while the sample that was processed based on the consideration there were 96 companies. The data analysis technique used logistic regression. The test results show that partially using the Wald test, only audit tenure has an effect on going concern audit opinions while other variables, namely liquidity, solvency and profitability, do not affect going concern audit opinions. Simultaneous test results using the Omnibus test show that audit tenure, liquidity, solvency and profitability affect going concern audit opinions. Based on the Cox & Snell's R Square value, the variability of the dependent variable (going concern audit opinion) which can be explained by the variability of the independent variables (audit tenure, liquidity, solvency and profitability) is only 3.3%. Keywords : Audit Tenure, Liquidity, Solvency, Profitability and Going Concern Audit Opinions.